2015
DOI: 10.3233/rnn-140418
|View full text |Cite
|
Sign up to set email alerts
|

Do all sub acute stroke patients benefit from robot-assisted therapy? A retrospective study

Abstract: Purpose: Upper limb robot-assisted rehabilitation is a highly intensive therapy, mainly recommended after stroke. Whether robotic therapy is suitable for subacute patients with severe impairments including cognitive disorders is unknown. This retrospective study explored factors impacting on motor performance achieved in a 16-session robotic training combined with standard rehabilitation. Methods: Seventeen subacute inpatients (age 53 ± 18; 49 ± 26 days post-stroke) were assessed at baseline using upper extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…A total of 850 studies were identified, 34 full texts were assessed for eligibility, and a total of 14 studies were included in this systematic review (see Figure 1, the PRISMA chart). A total of 13 studies 14,23,[33][34][35][36][37][38][39][40][41][42][43] included testing of correlations between USN and the affected UE capacity or recovery; of these, 11 studies 14,23,[33][34][35][36][37][38][39][40][41] were observational studies, and 2 studies 42,43 were a secondary analysis of an experimental design. Only 1 of the 14 included studies specifically researched the effect of an UE intervention provided to participants with USN.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 850 studies were identified, 34 full texts were assessed for eligibility, and a total of 14 studies were included in this systematic review (see Figure 1, the PRISMA chart). A total of 13 studies 14,23,[33][34][35][36][37][38][39][40][41][42][43] included testing of correlations between USN and the affected UE capacity or recovery; of these, 11 studies 14,23,[33][34][35][36][37][38][39][40][41] were observational studies, and 2 studies 42,43 were a secondary analysis of an experimental design. Only 1 of the 14 included studies specifically researched the effect of an UE intervention provided to participants with USN.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, our findings are in disagreement with Duret et al . [ 24 ], who found a negative correlation between MIul at T2 and MIul at T1. The reasons of such discrepancy can be found in the different sample sizes and in the different nature of the primary outcomes (our primary outcome is ADL, Duret’s primary outcome was motor function).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [ 16 ] on predictors of upper limb recovery after traditional arm therapy analysed several studies on this topic, and affirmed that measures of upper limb impairment and function were the most significant predictors (less impairment is associated with better recovery). However, literature on predictors of upper limb recovery after RT is limited and controversial [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to growing interest in developing devices that support the rehabilitation process and increase patients’ motivation ( Bertani et al, 2017 ; Fasola & Mataric, 2012 ; Maciejasz et al, 2014 ; Schoone et al, 2007 ). How to integrate productive rehabilitation tasks with motivational features is an especially challenging open question ( Duret et al, 2015 ; Nordin et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%